2019
DOI: 10.1155/2019/5604843
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis For Expression Profiles of lncRNAs and circRNAs in Rat Liver after Brain-Dead Donor Liver Transplantation

Abstract: The mechanisms underlying severe liver injury after brain-dead (BD) donor liver transplantation (BDDLT) remain unclear. In this study, we aimed to explore the roles of lncRNAs and circRNAs in liver injury after BDDLT. Rat liver injury was detected in the sham, BD, control, and BDDLT groups. We examined the expression profiles of lncRNAs and circRNAs in the livers of the BDDLT and control group using microarray analysis. The main functions of the differentially expressed genes were analyzed by gene ontology (GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…MiR-135a-5p may also act as a tumor suppressor in the development of colorectal adenomas and promote apoptosis of colon cancer cells ( 38 ). Here, we demonstrated that miR-135a-5p also targeted ATF3 ( 39 ). Our results also revealed the importance of miR-135a-5p in BTZ drug sensitivity in MM.…”
Section: Discussionmentioning
confidence: 77%
“…MiR-135a-5p may also act as a tumor suppressor in the development of colorectal adenomas and promote apoptosis of colon cancer cells ( 38 ). Here, we demonstrated that miR-135a-5p also targeted ATF3 ( 39 ). Our results also revealed the importance of miR-135a-5p in BTZ drug sensitivity in MM.…”
Section: Discussionmentioning
confidence: 77%
“…The mRNA levels of NLRP3, caspase-1, caspase-11, IL-1β, and IL-18 were measured by RT-qPCR. Total RNA was extracted from tissues using the TRIzol (Thermo Fisher Scientific, Shanghai, China), and reverse transcription was performed as described previously (26). Primers were designed based on the gene sequences acquired from PubMed.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%
“…The primers were synthesized by Invitrogen (Shanghai) Trading Co., Ltd., China, and are shown in Table 1. The primers were diluted appropriately, PCR amplification was performed, and RT-qPCR results were analyzed using a relative quantitative method as described previously (26).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%
“…The mRNA levels of NLRP3, caspase-1, caspase-11, IL-1β, and IL-18 were measured by RT-qPCR. Total RNA was extracted from tissues using the TRIzol (Thermo Fisher Scienti c, Shanghai, China), and reverse transcription was performed as described previously [20]. Primers were designed based on the gene sequences acquired from PubMed.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%
“…The primers were synthesized by Invitrogen (Shanghai) Trading Co., Ltd., China, and are shown in Table S1. The primers were diluted appropriately, PCR ampli cation was performed, and RT-qPCR results were analyzed using a relative quantitative method as described previously [20].…”
Section: Reverse Transcription-quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%